2006
DOI: 10.1016/j.brainres.2006.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Age- and transgene-related changes in regional cerebral metabolism in PSAPP mice

Abstract: In parallel to imaging studies in humans with Alzheimer's disease (AD), we have mapped brain metabolic activity in transgenic mouse models of AD. Our aim in both is to provide new surrogate markers of progression to help clarify disease mechanisms and rapidly screen candidate therapeutics. Since previous findings of preferential reductions in posterior cingulate glucose metabolism may have been confounded by morphological abnormalities in previously studied "PDAPP" transgenic mice, we first assessed hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 27 publications
(26 reference statements)
7
40
0
Order By: Relevance
“…In humans, most prominent reductions of FDG uptake were observed in the posterior cingulate cortex, precuneus, and parietotemporal areas, extending to the frontal cortex [9]. Similar findings have been reported for two different transgenic mouse models of AD (PDAPP and PSAPP), where significant reductions in [ 14 C]FDG uptake (∼−15%) as measured by ex vivo autoradiography were found in posterior cingulate cortex of aged transgenic as compared to wild-type mice [22,23]. In our study, these previous findings could not be confirmed as regional radioactivity uptake and ratios to whole brain were similar in both groups of animals after injection of FDG (Table 2).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In humans, most prominent reductions of FDG uptake were observed in the posterior cingulate cortex, precuneus, and parietotemporal areas, extending to the frontal cortex [9]. Similar findings have been reported for two different transgenic mouse models of AD (PDAPP and PSAPP), where significant reductions in [ 14 C]FDG uptake (∼−15%) as measured by ex vivo autoradiography were found in posterior cingulate cortex of aged transgenic as compared to wild-type mice [22,23]. In our study, these previous findings could not be confirmed as regional radioactivity uptake and ratios to whole brain were similar in both groups of animals after injection of FDG (Table 2).…”
Section: Resultssupporting
confidence: 78%
“…In our study, these previous findings could not be confirmed as regional radioactivity uptake and ratios to whole brain were similar in both groups of animals after injection of FDG (Table 2). Our failure to detect regionally increased [ 18 F]FDDNP retention and regionally decreased FDG retention in any brain area analyzed of transgenic animals is in all likelihood related to the limitations in spatial resolution of small animal PET as compared to 14 C-autoradiography [22,23]. Possible partial volume effects can lead to difficulties in volume definition and radioactivity measurements for small VOIs of mouse brain.…”
Section: Resultsmentioning
confidence: 71%
“…Although a given recording technique or analysis technique may reveal highly reliable differences for a specific region, it cannot automatically be concluded that this method is generally superior. Our study found areas of reduced activity in the caudal brain stem, cerebellum, and midbrain matching those identified in other studies (21). In addition, because the clusters of most significance were in the same place regardless of registration method and were away from the brain-skull interface, they were unlikely to be an artifact caused by misregistration, for example.…”
Section: Discussionsupporting
confidence: 88%
“…The ability to follow single animals or groups of animals using repeated scans should improve accuracy (by potentially reducing the effect of variability between animals) and reduce the number of animals required for studies, with the corollary of a significant lowering of costs when working with transgenic cohorts. However, attempts to measure changes in mouse brain metabolism have met with mixed results: uptake of 18 F-FDG correlated well with 14 C-DG uptake in normoglycemic animals (10), and 18 F-FDG PET has been used to reveal metabolic phenotypes in models of epilepsy (11,12) and Alzheimer disease (13)(14)(15)(16)(17)(18)(19)(20)(21). However, others have failed to detect differences in mouse models of Alzheimer disease (22,23) and the question may be raised of whether phenotypes are due to different acquisition and analysis methods yielding different sensitivities in identifying neuronal alterations.…”
mentioning
confidence: 99%
See 1 more Smart Citation